2
$\begingroup$

What we know is that $$x = \sum_{n=1}^{\infty}\frac{\sin(nx)}{n}(-2\cos(n\pi)), x \in (-\pi, \pi)$$ it was calculated using Fourier's series.
The task is to find the limit of
$$\sum_{n=1}^{\infty} \frac{\sin(n)}{n}$$ using the sum above.
I noticed that for $x = 1$ we have something similar in the first sum but I don't know how to finish the problem.

$\endgroup$
  • $\begingroup$ try $x=-1$ and think about $\cos(n\pi)$ $\endgroup$ – Marcel May 30 '17 at 22:04
4
$\begingroup$

Set $\pi-x$ as $x$ in your formula to get \begin{align} \pi-x&=\sum_{n=1}^\infty\frac{\sin(n\pi-nx)}{n}(-2\cos n\pi)= \sum_{n=1}^\infty\frac{\sin n\pi\cos nx-\cos n\pi\sin nx}{n}(-2\cos n\pi)=\\ &=\sum_{n=1}^\infty\frac{\sin nx}{n}(2\cos^2n\pi)=2\sum_{n=1}^\infty\frac{\sin nx}{n}. \end{align}

$\endgroup$
  • $\begingroup$ Very nice solution! :) Thank you $\endgroup$ – Hendrra May 31 '17 at 7:27
2
$\begingroup$

For any $z\in\mathbb{C}$ such that $|z|<1$ we have $$ \sum_{n\geq 1}\frac{z^n}{n} = -\log\left(1-z\right) \tag{1}$$ and if we set $z=\rho e^i$ for some $\rho=1-\varepsilon<1$ we get: $$ \sum_{n\geq 1}\frac{e^{in}}{n}\rho^n = -\log\left|1-\rho e^{i}\right|+i\varphi_\rho \tag{2}$$ where $\varphi_\rho$ is the angle between the line joining $\rho e^i$ with $1$ and the line joining $-1$ to $1$.
By switching to the imaginary parts we get: $$ \sum_{n\geq 1}\frac{\sin n}{n}\rho^n = \varphi_\rho \tag{3} $$ and by summation by parts / Abel's summation we are allowed to replace $\rho$ with $1$ in both sides: $$ \sum_{n\geq 1}\frac{\sin n}{n}=\color{red}{\frac{\pi-1}{2}}.\tag{4}$$

$\endgroup$
1
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

This becomes a straightforward application of the Abel-Plana Formula:

\begin{align} \left.\sum_{n = 1}^{\infty}{\sin\pars{n\theta} \over n}\right\vert_{\ \theta\ \not=\ 0} & = \theta\sum_{n = 1}^{\infty}\mrm{sinc}\pars{n\verts{\theta}} = -\theta + \theta\sum_{n = 0}^{\infty}\mrm{sinc}\pars{n\verts{\theta}} \\[5mm] & = -\theta + \,\mrm{sgn}\pars{\theta}\int_{0}^{\infty} {\sin\pars{n\verts{\theta}} \over n\verts{\theta}}\,\verts{\theta}\,\dd n + \theta\bracks{{1 \over 2}\,\mrm{sinc}\pars{0}} \\[5mm] & = -\theta + {1 \over 2}\,\pi\,\mrm{sgn}\pars{\theta} + {1 \over 2}\,\theta = \bbx{\pi\,\mrm{sgn}\pars{\theta} - 1 \over 2} \end{align}

The result is a valid one whenever

\begin{align} 0 & = \lim_{y \to \pm\infty}\bracks{% {\sin\pars{\theta\bracks{x + \ic y}} \over x + \ic y}\,\expo{-2\pi\verts{y}}} _{\ x\ \geq\ 0} \\[5mm] & = \lim_{y \to \pm\infty}\bracks{% {\sin\pars{\theta x}\cosh\pars{\theta y} + \ic\cos\pars{\theta x}\sinh\pars{\theta y}\over x + \ic y}\,\expo{-2\pi\verts{y}}} \end{align} It becomes clear that the above expression is true whenever $\ds{2\verts{\theta} - 2\pi < 0 \implies \bbx{\verts{\theta} < \pi}}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.